1986
DOI: 10.1159/000281209
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of the Bladder and Gravidity

Abstract: Following experimental investigations, the authors have performed bladder stimulator implantation for paralyzed bladder patients since 1969. Up to 1983 altogether 32 operations were carried out for bladder paralysis following 21 peripheral and 11 central neural lesions. The patients urinated without residue after the operation. The observations showed that regular use of the stimulator led to the elimination of reflux in patients who had vesicoureteral reflux before the operation. It was found that, if the sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…A limited number of treatments have been reported for restoring the control of the bladder 6, 7, 8, 9. The use of available oral drugs show limited clinical benefits,10, 11 and have numerous undesired side effects 12.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of treatments have been reported for restoring the control of the bladder 6, 7, 8, 9. The use of available oral drugs show limited clinical benefits,10, 11 and have numerous undesired side effects 12.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior study using current-response tests demonstrated no improvement in the peak bladder pressure that was induced with pulse duration longer than 400 s [15,19]. , Magasi et al [12,13] did not state their stimulating frequency; based on their extensive review of the literature they may have been using a frequency in the range of the 40 Hz tested here. A major difference in the stimulation methods between their study and ours was that Magasi et al used a much greater separation of the two stimulating surfaces within a bipolar set; one-fourth the distance around the bladder (horizontal plane of orientation) rather than the 5 mm separation used in this study.…”
Section: Problem With Stimulation Methodsmentioning
confidence: 62%
“…Current stimulation methods were not optimal as compared to the clinical study by Magassi et al [12,13] in areas of electrode characteristics and electrode geometry.…”
Section: Problem With Stimulation Methodsmentioning
confidence: 86%
See 2 more Smart Citations